THE RELATIONSHIP BETWEEN UNIVERSITIES AND COMPANIES IN THE REAL SECTOR OF THE ECONOMY - A. Lagzyan (Вестник университета)
The article describes the current state of innovative development of universities, their interaction with organizations of the real sector of the economy. The reasons for the lack of inter-action between science, education and business have examined. The positive changes in the case of application the cooperative potential of science, education and business have adduced. The anal-ysis of state stimulation and creation of such cooperative relations has conducted. In particular, the creation and development tool of engineering centers by which accelerates the process of innova-tion in universities and in the country as a whole, has considered. The relevance of the topic is de-termining by the current socio-economic situation in the country. At this stage, the task of the na-tional innovation system is to restore cooperation between universities and enterprises of the real sector of the economy for the implementation of global tasks.